Clinical Efficacy and Experimental Research Progress on Traditional Chinese Medicine Moxibustion Therapy in Ovarian Injury - Wang, Houpeng; Zhang, Ning; Zheng, Liping; Hu, Liaoliao (Chinese medicine and natural products, 2024)
This review summarizes the clinical efficacy and experimental research of traditional Chinese medicine (TCM) moxibustion in the intervention of ovarian injury. Clinical and experimental research results have shown that as a nonpharmacological treatment method, Chinese medical moxibustion therapy is of great significance in the treatment of ovarian injuries such as diminished ovarian reserve, polycystic ovarian syndrome, premature ovarian failure, and premature ovarian insufficiency. Moxibustion, heat-sensitive moxibustion, and electroacupuncture have significant effects in improving ovarian function, overall treatment efficacy, pregnancy rate, ovulation rate, and sex hormone levels and have higher safety. Their therapeutic mechanisms have also been demonstrated. In conclusion, TCM moxibustion therapy has a significant effect in the treatment of ovarian injury, providing a new option for the treatment of the ovarian injury.
Keywords: TCM moxibustion; ovarian damage; heat-sensitive moxibustion; electroacupuncture